2020
DOI: 10.1002/cppb.20117
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR/ttLbCas12a for in planta Gene Targeting in A. thaliana

Abstract: CRISPR/Cas systems enable gene editing through the induction of site‐specific DNA double‐strand breaks (DSB). However, the nature of the induced modification highly depends on the mechanism used for DNA DSB repair. Non‐homologous end joining (NHEJ)‐mediated targeted mutagenesis induced by CRISPR/Cas is an already standardly applied tool, which can lead to various different kinds of mutations at a specific genomic site. Nevertheless, precise genome modification using homologous donor sequences is still challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Notably, the GT alleles were inherited in the next generations (Figure 4 and Figure S16), indicating that the GT alleles were stably fixed into the tomato’s genome. This observation validates our KUDN-based GT tools and is consistent with other reports of GT in plants (Cermak et al, 2015; Dahan-Meir et al, 2018; Merker et al, 2020a; Merker et al, 2020b; Schindele et al, 2023; Wolter and Puchta, 2019). More importantly, the GT tools did not induce off-targeting activities in other genome sites (Figure S20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the GT alleles were inherited in the next generations (Figure 4 and Figure S16), indicating that the GT alleles were stably fixed into the tomato’s genome. This observation validates our KUDN-based GT tools and is consistent with other reports of GT in plants (Cermak et al, 2015; Dahan-Meir et al, 2018; Merker et al, 2020a; Merker et al, 2020b; Schindele et al, 2023; Wolter and Puchta, 2019). More importantly, the GT tools did not induce off-targeting activities in other genome sites (Figure S20).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we established a GT system based on a geminiviral replicon and the CRISPR-LbCas12a nuclease (Vu et al, 2020) that was improved by using the temperature-tolerant (ttLbCas12a) variant (Huang et al, 2021; Merker et al, 2020b; Schindele et al, 2023; Vu et al, 2021a) and further enhanced by chemical treatments for cNHEJ suppression (Vu et al, 2021a). However, it is still challenging to conduct GT experiments without allele-associated markers for selecting GT events, which limits the applications of GT in tomato and other plants.…”
Section: Introductionmentioning
confidence: 99%
“…Our data provide an example of how relatively high frequency GT can be achieved in Arabidopsis even with a straightforward protocol. Additional refinements in terms of the type of CAS gene used, for example intronized CAS9 (Grutzner et al, 2021) or LbCas12a (Merker et al, 2020; Wolter and Puchta, 2019), or refinements in the composition of the donor construct and the way in which the donor construct is delivered are likely to further increase GT frequency. As GT becomes more feasible, particularly in model plants, the next step in applying it for research is to better understand when it would be advantageous compared to the more traditional approach of transgenic complementation of a mutant with constructs encoding the protein of interest fused to a tag and expressed under control of its native promoter.…”
Section: Discussionmentioning
confidence: 99%
“…In single stage GT, it was reported that use of the egg cell-specific promoter EC1.1 could enhance heritable GT (Wolter et al, 2018). Other experiments revealed that co-expression of chromatin remodelers with the GT construct (Shaked et al, 2005), deletion of a DNA polymerase theta involved in NHEJ (van Tol et al, 2022), heterologous expression of recombinases to promote homologous recombination (Barakate et al, 2020), use of viral replicon expression system to generate increased levels of donor DNA and CAS9 (Cermak et al, 2015; Vu et al, 2020), or use of other nucleases such as CAS12a (Huang et al, 2021; Merker et al, 2020) could enhance GT at different test loci assayed in each study. While these studies all reported ways to enhance GT, they differed with respect to the tested loci, whether the GT test involved insertion of a new sequence (such as YFP or RFP) or just replacement of existing sequence to correct or introduce a readily assayed mutation, and the length of homology arms used in the DNA donor constructs.…”
mentioning
confidence: 99%
“…To specifically monitor the dynamics of selected single loci, the parS sequence would need to be inserted at a precise position within the desired locus. A recent approach that combine CRISPR-Cas9 technology and a homologous recombination-donor cassette can generate knock-in A. thalian a plants (Miki et al, 2018 ; Wolter et al, 2018 ; Merker et al, 2020 ). The implementation of the parS knock-in strategy will really improve the innocuity of this approach on the local chromatin state and should strongly reduce any bias on its nuclear positioning.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%